Nanosystems as Vehicles for the Delivery of Antimicrobial Peptides (AMPs) - Ángela Martin-Serrano; Rafael Gómez; Paula Ortega; F. Javier de la Mata (MDPI AG, 2019)
Recently, antimicrobial peptides (AMPs), also called host defence peptides (HDPs), are attracting great interest, as they are a highly viable alternative in the search of new approaches to the resistance presented by bacteria against antibiotics in infectious diseases. However, due to their nature, they present a series of disadvantages such as low bioavailability, easy degradability by proteases, or low solubility, among others, which limits their use as antimicrobial agents. For all these reasons, the use of vehicles for the delivery of AMPs, such as polymers, nanoparticles, micelles, carbon nanotubes, dendrimers, and other types of systems, allows the use of AMPs as a real alternative to treatment with antibiotics.